A systematic review of volar locking plate removal after distal radius fracture. Issue 12 (December 2017) - Yamamoto, Michiro; Fujihara, Yuki; Fujihara, Nasa; Hirata, Hitoshi
Abstract: Background: Indication of volar locking plate (VLP) removal after bony healing of distal radius fracture (DRF) is controversial. Studies with various range of removal rate were reported. The purpose of this systematic review was to investigate the frequency and the reasons of hardware removal over the world. We hypothesized that more frequent VLP removal contribute to better clinical outcomes. Methods: The authors searched all available literature in the PubMed and EMBASE databases for articles reporting on outcomes of treatment using VLP for DRF. Data collection included hardware removal rate, complication rate, clinical and radiological outcomes. We analyzed correlation between hardware removal rate with clinical and radiological outcomes. Results: A total of 3472 articles were screened, yielding 52 studies for final review. The mean hardware removal rate was 9%, ranging from 0 to 100%. The mean removal rate in studies from France, Norway, Japan, and Belgium was as high as 19%. The mean removal rate in studies from the US was low (3%). The most frequent reasons for extraction were routine removal (22%), tendon irritation or tenosynovitis (14%), hardware problem (14%), and patient' request (13%). Although routine removal and patient' request were not counted as complication, correlation between removal rate with complication rate was strong (rho = 0.64, p < 0.001). Correlations between clinical and radiological outcomes were week except for volar tilt (rho = −0.42, p = 0.009). Conclusions: There was a diversity of removal rate and reasons in the studies over the world. High frequent VLP removal did not contribute to better clinical outcomes.